(untitled) (Caderno de Ciências Agrárias, 2017)
Resumo: This study aimed to evaluate the use of Box and Jenkins methodology in modeling of behavior of the prices of the cubic meter of coal in the northern region of Minas Gerais and predict future trends. Was used a time series of monthly prices of coal within the period from January 2010 to may 2017 and processing has been performed in Eviews 7.0. The model that best fit the behavior of the database was the ARIMA (1, 1, 1) and the rates laid down for the months of June to December 2017 were respectively R108,00, R107,23, R106,61, R105,93, R105,12, R104,23, R103,37 showing a downward trend as the occurred during the year 2016. It is concluded that the methodology Box and Jenkins is suitable to perform price forecasts of coal in the North of Minas Gerais and can be used as a subsidy to decision-making in forest planning, taking care to stick to other relevant factors such as the conditions soil and climate. Abstract: This study aimed to evaluate the use of Box and Jenkins methodology in modeling the behavior of prices of the cubic meter of coal in the northern region of Minas Gerais and predict future trends. A time series of monthly prices of coal within the period was used from January 2010 to may 2017 and processing has been performed in Eviews 7.0. The model that best fits the behavior of the database was the ARIMA (1, 1, 1) and the rates laid down between June and December 2017 were respectively R108,00, R107,23, R106,61, R105,93, R105,12, R104,23, R103,37, showing a downward trend as the one from 2016. It is concluded that the methodology of Box and Jenkins is suitable to perform price forecasts of coal in the North of Minas Gerais and can be used as a subsidy to decision-making in forest planning, highlighting other relevant factors such as soil and climate conditions